La Grande muraille verte au Sahel : entre ambitions globales et ancrage local - Ronan Mugelé (Bulletin de l’Association de Géographes Français)
The Great Green Wall is the name of a Sahelian program which has been launched in 2005 with the support of the African Union to combat the growing process of desertification. In a geographical and critical perspective, this program is analysed as a multi-scale and multi-actors construction. Highly influenced by former environmental projects, the Great Green Wall is also deeply linked to global dynamics through new political and financial opportunities. The example of its difficult territorialisation in northern Senegal is analysed as the result of this glocal construction.